Penggunaan Campur Kode Pada Novel Banjarmelati Karya Ahmad Zaenudin (Kajian Kesusastraan) - Wyandha, Brillita Naja Ein; Kurnia, Ita (Jurusan Pendidikan Bahasa & Sastra Indonesia, Universitas Negeri Gorontalo, 2023)
This study analyzes the presence of code-mixed forms in Ahmad Zaenudin's novel Banjarmelati. This study aims to describe: 1) The use of code-mixed forms in Ahmad Zaenudin's novel Banjarmelati. 2) Knowing the function of code mixing in the novel Banjarmelati by Ahmad Zaenudin. This study uses a qualitative method, namely descriptive analysis. In this study using data in the form of dialogue between characters. The research data was sourced from the novel Banjarmelati by Ahmad Zaenudin. The data collection technique in this study is by observing method and note-taking method, because the data source is in the form of text. Based on the research results, it was found that there is a form of code mixing in the novel Banjarmelati by Ahmad Zaenudin. The code-mixing functions that cause code-mixing to occur in the novel Banjarmelati by Ahmad Zaenudin include: 1) Making it easier to convey intentions, 2) Demonstrating familiarity, 3) Vocabulary requirements, 4) Talking about certain topics, 5) Demonstrating regional languageKata kunci: Literature; Mixed code; Novel Banjarmelati.